Basic Business Communication: Skills For Empowering the Internet Generation - V.Lesiker Raymond (MC Graw Hill, 2004)
Through nine previous editions, Basic Business Communication has been popular for its ability to provide readers with solid how-to skills in every area of business communication. This latest edition examines current technologies including wireless, Net meeting, and Web-based research. A stimulating CDROM features video clips demonstrating good and bad communication, useful writing templates, and more.